Study of effective factors on the rate of citizen\'s trust to the municipal performance of Sari city - shahram mollania jelodar; maryam malmir; seyed Hassan rasouli; zahra tabali (تحقیقات کاربردی علوم جغرافیایی)
Many social researchers and experts has emphasized on the importance of confidence in the society. Municipality as one of the biggest social organizations can enjoy more productivity and efficiency when attracts citizens' confidence as a social and spiritual capital, and uses it in the way of organizational objectives and town development. This research aims to examine the extent of citizens' confidence in municipality performance and its effective factors.